Design, Synthesis, and Biological Evaluation of Quinoxaline Bearing Tetrahydropyridine Derivatives as Anticancer, Antioxidant, and Anti-Tubercular Agents - Pavale, Ganesh; Acharya, Poornima; Korgavkar, Nilesh; Ramana, M. M. V. (Current Computer - Aided Drug Design, 2022)
Background: Quinoxaline and Tetrahydropyridine derivatives showed various biological properties. The combination of these two scaffolds may contribute to good biological activity and may give novel and efficacious bioactive candidates. Objective: The present study aimed to identify bioactive agents with quinoxaline bearing tetrahydropyridine derivatives possessing anticancer, antioxidant, and anti-tubercular agents. Methods: A series of novel quinoxaline bearing tetrahydropyridine derivatives have been designed and synthesized in good yields. The synthetic protocol involves three-component Povarov reactions of 6-amino quinoxaline, propenyl guaethol, and substituted aldehydes using BF3·OEt2 as catalyst. The newly synthesized molecules were evaluated for their anticancer activity against four cell lines, i.e. A-549, MCF-7, PC-3, and HepG2. Results: The results from in vitro assay indicated that compound 4a proved to be as potent as the standard drug adriamycin against all cell lines with GI50 values <10 μg/ml. Compounds 4b, 4f, and 4i exhibited good cytotoxicity against A-549 cell line. All synthesized molecules were evaluated for their antioxidant activity and the results revealed that the compounds 4a, 4b, and 4i showed promising antioxidant activities against DPPH and H2O2 scavenging. In addition, the anti-mycobacterial activity of the synthesized compounds against MTB H37Rv strain was determined using the MABA method. The results indicate that the compounds 4a, 4b, 4g, and 4i showed better antimycobacterial activity than the standard drugs pyrazinamide, ciprofloxacin and streptomycin with an MIC value of 1.6 μg/ml. Furthermore, molecular docking studies and ADME properties showed good pharmacokinetic profile and drug-likeness properties. Conclusion: These studies showed that a series of novel quinoxaline bearing tetrahydropyridine derivatives exhibit anticancer, anti-mycobacterial, and antioxidant activities.
Keywords: molecular docking